Discourses of Division: An Ethnography of the Oklahoma Proud Boys - Chandler, Zachary (My University, 2022)
As a self-described group of "Western chauvinists," the Proud Boys have become lodged within the national consciousness because of their participation in historical and contemporary discourses concerned with fascism, militancy, and White supremacy. Members of Proud Boys chapters from across the nation have been continually vilified for espousing racist, misogynist, homophobic, and other repugnant ideologies. This study harnessed the methodological toolkit of ethnography to understand how members of the Oklahoma Proud Boys find meaning by joining this fraternal order. It takes as its point of departure an analysis of three competing strains of thought that make assertions about racial formations, specifically whiteness. The first, voiced by members of the Oklahoma Proud Boys ties whiteness a set of gendered and classed values, practices, experiences, and institutions while reducing it to a dichotomy of moral and immoral living. The second, voiced by popular pundits and best-selling authors that analyze the contemporary as a reflection of White supremacy and prescribe a set of tools for combatting this. Among this strain the basic assumptions about whiteness and how it can be challenged can be considered a reductive binary of racism and antiracism. Finally, a third body of literature is voiced by scholars who offer an alternative approach to the ways that racial formations operate as intersectional and contingent upon particular histories, power structures, and social relations.
Keywords: proud boys; whiteness; discourse